Ecological restoration in Mexico: An emerging discipline in a deteriorated country - Calva-Soto, Karina; Pavón Hernández, Numa Pompilio (Instituto de Ecología, A.C., 2018)
Terrestrial ecosystems are perturbed by human activities, and many of them need to be restored so biodiversity and environmental services can recover. However, ecological restoration is incipient in Mexico as a multidisciplinary issue that still requires further advances in theory and practices. Publications on ecological restoration in Mexico were analyzed to provide an insight into the current state of knowledge on the subject and identify gaps, biases, and progress. We used databases on the web, from which 20 764 references were obtained and 402 were selected, which met all of the requirements. All selected references were reviewed and classified considering various criteria. Among these, research questions in ecological restoration: why, what, how, where and when to restore. From the total, 32% were studies of ecological restoration sensu stricto. In eight states no reference studies were found. Chiapas and Veracruz were the most cited. Most work was conducted in tropical (43%) and temperate forests (13%). Only 10% of the references included all restoration research questions. In Mexico, ecological restoration is an emerging discipline, which despite the political, economic and social complications of the country, has received increased attention by different working groups, principally in the last 10 years. It should be noted that so far, studies continue to have a focus on restoration ecology, it being necessary to develop strategies to help increase ecological restoration projects aiming to restore degraded ecosystems.